2010
DOI: 10.1007/s00702-010-0378-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of the POMC gene promoter is associated with craving in alcohol dependence

Abstract: Hypothalamic-pituitary-adrenal (HPA) axis dysfunction has been implicated in the pathogenesis of addictive behaviour and especially in alcohol craving. The pro-opiomelanocortin gene (POMC), encoding a 241 amino acids stretching polypeptide hormone precursor, plays an important role in the regulation of the HPA, and is prone to epigenetic regulation due to promoter-related DNA methylation. Aim of the present study therefore was to investigate possible differences in promoter-related DNA methylation in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 20 publications
1
53
0
1
Order By: Relevance
“…These 8 CpGs grouped into 1 cluster comprising the CpGs at position −399 to −328 (relative to exon 1). This cluster (referred to as CpG cluster) was identical to the cluster described by Muschler et al 39 in alcohol-dependent patients. Using the Matinspector of Genomatix, 47 several putative transcription factor-binding sites within the identified cluster 1 were found, among them the previously described transcription factor module containing transcription factor binding sites for Neuro-D1, pituitary cell-restricted T box factor, and pituitary transcription factor.…”
Section: Bisulfite-sequencing Of the Promoter Of Pomcsupporting
confidence: 77%
See 2 more Smart Citations
“…These 8 CpGs grouped into 1 cluster comprising the CpGs at position −399 to −328 (relative to exon 1). This cluster (referred to as CpG cluster) was identical to the cluster described by Muschler et al 39 in alcohol-dependent patients. Using the Matinspector of Genomatix, 47 several putative transcription factor-binding sites within the identified cluster 1 were found, among them the previously described transcription factor module containing transcription factor binding sites for Neuro-D1, pituitary cell-restricted T box factor, and pituitary transcription factor.…”
Section: Bisulfite-sequencing Of the Promoter Of Pomcsupporting
confidence: 77%
“…We determined DNA methylation of the whole POMC promoter as well as a DNA methylation of a specific cluster of CpG islands within the promoter known to play a crucial role for POMC expression. 39,40 The extent of malnutrition was characterized by plasma leptin concentrations. Leptin is a nutritionally regulated hormone primarily secreted by adipocytes that affects food intake and energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Moreover, levels of alcohol dependence negatively correlated with the degree of methylation in the NR2B gene promoter. 25 It has also been shown that alcohol-dependent individuals requiring pharmacological treatment (clomethiazole) to help curb their craving during abstinence have higher levels of CpG methylation in a discrete portion of the gene promoter for proopiomelanocortin (POMC), 26 with POMC already known to play a role in alcohol-drinking behavior. 27 Recent evidence similarly suggests that the methylation status of the gene promoters for monoamine oxidease-A (MAOA) and Catechol-O-methyltransferase (COMT), two enzymes involved in catecholamine neurotransmitter metabolism, may also influence vulnerability to develop alcohol and/or tobacco dependence.…”
Section: Addiction and Dna Methylationmentioning
confidence: 99%
“…25,26 For example, expression of the NR2B subunit of the N-methyl-D-aspartate (NMDA) glutamate receptor is increased during alcohol withdrawal in human drinkers, as measured in circulating white blood cells, suggesting that NR2B-containng NMDA receptors may contribute to the expression of this aversive behavioral state. 25 Moreover, levels of alcohol dependence negatively correlated with the degree of methylation in the NR2B gene promoter.…”
Section: Addiction and Dna Methylationmentioning
confidence: 99%